2014
DOI: 10.1210/me.2013-1413
|View full text |Cite
|
Sign up to set email alerts
|

Minireview: Metabolism of Female Reproduction: Regulatory Mechanisms and Clinical Implications

Abstract: Female fertility is highly dependent on successful regulation of energy metabolism. Central processes in the hypothalamus monitor the metabolic state of the organism and, together with metabolic hormones, drive the peripheral availability of energy for cellular functions. In the ovary, the oocyte and neighboring somatic cells of the follicle work in unison to achieve successful metabolism of carbohydrates, amino acids, and lipids. Metabolic disturbances such as anorexia nervosa, obesity, and diabetes mellitus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 196 publications
0
41
0
4
Order By: Relevance
“…Within the oocyte, pyruvate is converted in mitochondria to acetyl CoA, which enters the tricarboxylic acid (TCA) cycle and electron transport chain to produce adenosine triphosphate (ATP) (61). The oocyte in turn ensures its own delivery of pyruvate by up-regulating glycolytic genes in cumulus cells (7,64).…”
Section: Cellular Metabolism Glucose Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the oocyte, pyruvate is converted in mitochondria to acetyl CoA, which enters the tricarboxylic acid (TCA) cycle and electron transport chain to produce adenosine triphosphate (ATP) (61). The oocyte in turn ensures its own delivery of pyruvate by up-regulating glycolytic genes in cumulus cells (7,64).…”
Section: Cellular Metabolism Glucose Metabolismmentioning
confidence: 99%
“…With increased glucose, oxygen, and pyruvate consumption during oocyte maturation, the oocyte also interacts with cumulus cells to regulate delivery of amino acids and cholesterol for other cellular processes (7,46,(85)(86)(87)(88). Human oocytes with high amino acid turnover in vitro (i.e., valine and isoleucine) have lower developmental potential than those with low amino acid turnover (89).…”
Section: Amino Acid Turnovermentioning
confidence: 99%
See 1 more Smart Citation
“…Although the mechanisms mediating the influence of metabolism and nutrition on fertility are cur-rently unclear, a strong association between metabolic disorders and infertility is undeniable [23]. Seli e and Wathes DC reported that obesity and overweight, which are characterized by lipid and glucose metabolic disorders, are significantly involved in the incidence of polycystic ovary syndrome and impaired natural fertility [29,35].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity and/or overweight as well as underweight are negatively associated with female fertility [111,112]. A decreased success in spontaneous conception, an increased rate of anovulation, and increased risks of miscarriage have been reported in obese women at reproductive age [113]. Furthermore, there are indications that maternal obesity may affect the reproductive capacity in their children [114].…”
Section: Energy Status and Female Reproductionmentioning
confidence: 99%